P334 Extreme precipitation, turbidity, drinking water and acute gastro-intestinal illness in a canadian surface drinking water system: mechanisms and opportunities to build resilience to climate change. (1st September 2016) - Takaro, Tim K; Chhetri, Bimal; Mak, Sunny; Otterstatter, Michael; Balshaw, Robert; Sobie, Stephen; Henderson, Sarah; Zubel, Mark; Len, Marcus; Brubacher, Jordan; Zickfeld, Kirsten; Fleury, Manon; et al.
Abstract : Introduction: Climate change is expected to increase the burden of waterborne acute gastrointestinal illness (AGI) with the increased frequency and intensity of extreme precipitation events. Turbidity in source water is a risk factor. Here we investigate the relationship between extreme precipitation, turbidity and parasitic AGI. Further, we project the impact of climate change on these illnesses at a watershed level. Methods: All 1997–2009 reported cases of cryptosporidiosis and giardiasis in a population served by a municipal surface drinking water system were analysed using distributed lag non-linear models. Precipitation was assessed for a lag up to six weeks, and adjusted for seasonality, secular trend, preceding dry/wet period and holiday effects. The mean annual case counts were predicted for 2060–2069 using downscaled daily precipitation projections from 10 global climate models under a moderate emissions growth scenario. Results: Including 7422 cases, a significant increase in cryptosporidiosis and giardiasis 5–6 weeks after extreme precipitation (>90th percentile) was found during the study period. The highest rate ratio (1.17; 1.07–1.24) was identified for a lag of five weeks. A preceding dry period further increased the risk, which appears to be driven by increases in turbidity. Temperature did not contribute significantly to this risk. Climate models indicate decreases in average weekly and extreme precipitation during dry seasons in the 2060s, but increases in rainy seasons compared with 2000–2009. The overall annual disease burden increased by 6.3 % −14.2% (ensemble mean 12.1%). Discussion: We found a significant risk of waterborne illness associated with extreme precipitation events in a large and well-protected municipal drinking water system. The effects were most pronounced following a dry period. To try and reduce these future risks additional filtration of finished water is being deployed for these sources. There is a need to increase resilience in water systems to address the impacts due to climate change.